A Comparative Study of Quality of Life in Persons With Irritable Bowel Syndrome and Inflammatory Bowel Disease. (July 2015) - Blagden, Sarah; Kingstone, Thomas; Soundy, Andrew; Lee, Rhonda; Singh, Sukhdev; Roberts, Lesley
<x xml:space="preserve">Abstract</x> Irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder; however, it remains poorly understood. Inflammatory bowel disease (IBD) is a chronic, organic bowel disease characterized by young age of onset, debilitating symptoms, and invasive and toxic treatment options. This study aimed to determine the impact of IBS and IBD on health-related quality of life (HRQoL) and the ways by which these conditions affect HRQoL, with the purpose of informing nurse specialists in gastroenterology who are best placed to support HRQoL improvements. Quality of life, symptom, and demographic data were collected from patients with IBS and IBD and tabulated and examined. Analysis of data demonstrated that HRQoL is significantly lower in IBS than in IBD. However, the ways by which these two conditions affect HRQoL differs, with greater impairments in social and emotional aspects of life in individuals with IBS. Bowel symptoms were the same or worse in IBD.